The Antihyperglycemic Effects of Glibenclamide and Matoa Leaves Extract (Pometia pinnata J.R. Forst & G. Forst) On Alloxan-Induced Rat - Niam, Muhammad Labib Qotrun; Ziah, Nur Khalida; Fadhilah, Arini (Universitas Muhammadiyah Surakarta, 2024)
Glibenclamide (GLI) orally treatment for diabetes mellitus has adverse effects, such as hypoglycemia and weight gain. A synergistic effect achieved through the combination of natural constituents provides an alternative method for reducing adverse effects. The aim of this study was to investigate the contribution of 50% ethanol leaves extract (EEDM) to the administration of GLI in alloxan induced rats. A total of 20 rats were divided into 4 groups, namely normal control (NC), negative control, GLI 5 mg/KgBW group, and the combination of GLI 5 mg/KgBW and EEDM 100 mg/KgBW. Fasting blood sugar data (FBG), body weight, urine chemistry for 15 days of treatment measured. The results show that the ability of the GLI-EEDM combination to lower FBG is more effective and can withstand the hypoglycemic effects of GLI, in addition to improving the secretion of glucose in the urine.